Epithelial inducible nitric oxide synthase activity is the major determinant of nitric oxide concentration in exhaled breath. Issue 9 (27th August 2004) - Lane, C; Knight, D; Burgess, S; Franklin, P; Horak, F; Legg, J; Moeller, A; Stick, S
Abstract : Background: The fractional concentration of nitric oxide (NO) in exhaled breath (FeNO ) is increased in asthma. There is a general assumption that NO synthase (NOS) 2 in epithelium is the main source of NO in exhaled breath. However, there is no direct evidence to support the assumption and data from animal models suggest that non-inducible NOS systems have important roles in determining airway reactivity, regulating inflammation, and might contribute significantly to NO measured in exhaled breath. Methods: Bronchial epithelial cells were obtained from healthy, atopic, and asthmatic children by non-bronchoscopic brushing. Exhaled NO (FeNO ) was measured directly using a fast response chemiluminescence NO analyser. RNA was extracted from the epithelial cells and real time polymerase chain reaction was used to determine the expression of NOS isoenzymes. NOS2 was examined in macrophages and epithelial cells by immunohistochemistry. Results: NOS1 mRNA was not detectable. NOS3 mRNA was detected in 36 of 43 samples at lower levels than NOS2 mRNA which was detectable in all samples. The median FeNO was 15.5 ppb (95% CI 10 to 18.1). There was a significant correlation between FeNO and NOS2 expression ( R  = 0.672, p<0.001). All epithelial cells exhibited NOS2 staining, whereas staining in the macrophages was variable and not related to phenotype. Conclusions: Only NOS2 expression was associated with FeNO in respiratory epithelial cells obtained from children ( R  = 0.672; p<0.001). This suggests that FeNO variability is largely determined by epithelial NOS2 expression with little contribution from other isoforms.